(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Inferior wall myocardial infarction (MI) is often associated with conduction disturbances due to its impact on the atrioventricular (AV) node, primarily supplied by the right coronary artery. Identifying the frequency and type of AV blocks in such patients is essential for prompt management. Objective: To determine the frequency of various degrees of AV block in patients presenting with inferior wall MI. Methods: A descriptive cross-sectional study was conducted at Rehman Medical Institute, Peshawar, from August to November 2024. A total of 192 patients aged 35–70 years with confirmed inferior MI were enrolled using a convenient sampling technique. Patients with pre-existing AV block or conduction abnormalities from other causes were excluded. Standard 12-lead ECG was used for diagnosis. Patients were categorized into AV block-positive and AV block-negative groups. AV blocks were further classified as first-degree, second-degree (Mobitz Type I and II), or third-degree. Results: Out of 192 patients, 58 (30%) developed AV blocks. First-degree AV block was observed in 28 patients (15%), second-degree Mobitz Type I in 4 patients (2%), and third-degree AV block in 25 patients (13%). No cases of Mobitz Type II were detected. AV blocks were more frequent in males and in patients with STEMI. Conclusion: Atrioventricular blocks are a common complication of inferior wall MI, affecting approximately 30% of patients. First-degree and third-degree blocks were the most prevalent. These findings highlight the importance of early ECG evaluation and continuous cardiac monitoring to guide timely management.